Аўыл хожалығының баслы зыянкеси - жалпақ тисли крыса (nesokiya indica gray) менен гүрес усыллары (SCIENCE and SOCIETY, 2022)
The article provides information on how to combat small rodents, the most common pests of agriculture, milk thistle - the rattlesnake and prevent large-scale economic damage. One of the main methods of struggle is the selection and application of a method that gives a concrete and clear entrance to the rescue of ten damaged objects from the rat by the method of harmless struggle.